ASEPSY AND ANTISEPSY IN DENTO-ALVEOLAR SURGERY - Ovidiu Mihail Ștefănescu (Romanian Journal of Oral Rehabilitation, 2018)
The human body is a wonderful work of balance, self-defense and perfection; our duty is to keep its fully integrity. When we suppress an element from those that are not essential, nature does a while, but the "hour" of decompensation is inevitable. We must prevent it and strive to counteract its effects. We can do it much more often than we believe. In oral and maxillo-facial surgery, postoperative disease is rapidly established within hours after surgery, indicating especially the origin of the nervous system more than the toxic origin incriminated in the forms of postoperative disease, known in general surgery. The postoperative disease comprises a complex of neurovegetative, endocrine, humoral, circulatory and homoleucocity disorders triggered by the operative act in the body due to triggered and predisposing causes, clinical manifestations being dominated by local phenomena. Asepsis and antisepsis are the necessary and inseparable elements of the disinfection process; they complement each other and are used simultaneously, making together sterilization, which is the most complete form of disinfection.